Sociodemographic, neuropsychiatric and cognitive characteristics of pathological gambling and impulse control disorders NOS in Parkinson׳s disease - Pontieri, Francesco E.; Assogna, Francesca; Pellicano, Clelia; Cacciari, Claudia; Pannunzi, Sara; Morrone, Annalucia; Danese, Emanuela; Caltagirone, Carlo; Spalletta, Gianfranco (European neuropsychopharmacology, 2015)
Despite of previous evidence supporting the association between impulse control disorder (ICD) and several demographic, clinical and therapeutic features in Parkinson׳s disease (PD), the relationships between pathological gambling (PG) or other variants of ICD (ICD-NOS) and specific neuropsychiatric or cognitive domains are not entirely defined. In this study, 155 PD patients without dementia or cognitive impairment underwent: i. the ICD diagnoses, using the Questionnaire for Impulsive–Compulsive Disorders, ii. the mood and anxiety disorders diagnoses, according to the DSM-IV-TR criteria, and iii. a comprehensive battery for measuring severity of psychopathology and neuropsychology domains. Patients were divided in those with pathological gambling (PG), ICDs not otherwise specified (ICD-NOS), or the lack of ICD (No-ICD). There was a progression in age and age at onset from the younger PG subjects throughout ICD-NOS to No-ICD. PG and ICD-NOS subjects had longer disease duration and were taking significantly higher dosages of antiparkinsonian drugs than No-ICD ones. PG subjects had significantly higher severity of depressive and anxious symptoms with respect to the other 2 groups. Both PG and ICD-NOS subjects suffer from increased severity of psychotic symptoms than No-ICD ones. The 3 groups did not differ in any cognitive measure. Our results support the concept that the different sociodemographic and neuropsychiatric profiles of PD patients are associated with different ICDs. Moreover, we clearly demonstrate the lack of relationship between ICD and cognitive performances in undemented PD patients.